The rising tensions between religion, eroticism and art: The Martyrdom of Saint Sebastian - Santos, Alexandre (PORTO ARTE: Revista de Artes Visuais, 2017)
This article proposes a reflection on the Martyrdom of Saint Sebastian, which blends religious practice and erotic pleasure. Georges Bataille’s assumption that eroticism and religiosity are complementary cultural constructions in search of overcoming the finitude and the discontinuity between human beings encompasses the presence of St. Sebastian in the contemporary art related to the photographic image. The implied cult of the Holy soldier’s sensuality in Renaissance and baroque paintings turns into explicit appropriation in the homoerotic iconography of the 20th century, as we can see in the openly biographical translations of the theme in the performance pictures by Yukio Mishima and Luigi Ontani and in Derek Jarman’s film "Sebastiane".